A special double lumen tube for use in pigs is suitable for different lung ventilation conditions. (December 2020) - Lesser, Thomas; Braun, Conny; Wolfram, Frank; Gottschall, Reiner
Abstract: Previous studies of haemodynamic and blood gas variables during one-lung ventilation in pigs have used a double lumen tube designed for use in humans. However, because of interspecies differences in bronchial anatomy, a special design for pigs is required. In this study, we evaluated a new left-sided double lumen endobronchial tube designed for use in pigs under different lung ventilation conditions. Ten female pigs (weighing 35–40 kg) were transorally intubated, first with a single lumen tube and then with the left-sided double lumen tube for pigs, and mechanically ventilated. Haemodynamic and blood gas variables were recorded before and after intubation with the double lumen tube and before and after one-lung flooding of the left lung with saline solution. Each pig was repositioned (left lateral, to dorsal, to right lateral) every 30 min during one-lung flooding. Bronchoscopy and thoracic radiography were performed at fixed intervals. Blood gas variables during two-lung ventilation were not impaired by intubation with the double lumen endobronchial tube for pigs, compared with intubation with the single lumen tube. Haemodynamic and blood gas variables were not impaired by one-lung flooding. Complete flooding of the left lung was achieved for all pigs. Two-lung ventilation to reventilate the previously flooded lung provided complete air filling for all pigs. Use of this tube resulted in lung separation without obstruction of bronchi or resultant atelectasis. In this study, the new double lumen tube for pigs was safe for one-lung flooding and prevented fluid entry into the non-flooded lung. Highlights: DLETs designed for use in humans are not suitable for use in pigs. A DLET designed for use in pigs provides a lung separation without bronchial obstruction and allows transorally intubation. By the DLET haemodynamic and blood gas variables are not impaired, compared with intubation with the single lumen tube. The new DLET is safe for one-lung flooding and prevents fluid entry into the non-flooded lung. The haemodynamic and gas exchange variables are not impaired after one-lung flooding via the DLET.